An Implementation Approach Comparison of a Child Care Center-Based Obesity Prevention Program. Issue 2 (February 2021) - Natale, Ruby A.; Atem, Folefac; Weerakoon, Sitara; Lebron, Cynthia; Mathew, M. Sunil; Sardinas, Krystal; Chang, Catherina; Shelnutt, Karla P.; Spector, Rachel; Altare, Fiorella; Messiah, Sarah E.
ABSTRACT: Objective: To compare the effectiveness of the Healthy Caregivers-Healthy Children (HC2) phase 1 (2011–2014) and 2 (2015–2018) child care center (CCC)-based obesity prevention intervention(s) on child dietary practices and body mass index percentile (PBMI) outcomes over 2 years. Phase 1 was implemented via a university-based research team, and phase 2 was delivered via a train-the-trainers approach (university-based research team trains preschool-based coaches, who in turn train CCC teachers to implement and disseminate HC2). Methods: Phase 1 and 2 were both cluster randomized controlled trials of the HC2 obesity prevention intervention. Phase 1 was composed of 1224 children in 28 CCCs (12 intervention and 16 control). Phase 2 was composed of 825 children in 24 CCCs (12 intervention and 12 control). Both phases included CCCs serving low-resource, predominantly ethnic minority families. Results: The mean rate of weekly fruit consumption significantly increased (β = 0.16, p = 0.001) in phase 1, whereas vegetable intake significantly increased (β = 0.16, p = 0.002) in phase 2 intervention CCCs. Fried (β = −0.36, p < 0.001), fast (β = −0.16, p = 0.001), and other unhealthy food (β = −0.57, p < 0.001) consumption significantly decreased in phase 1 only. The mean rate of snack food consumption significantly decreased in phase 2 (β = −0.97, p < 0.001). Mean child PBMI remained in the healthy range over 2 years for all groups in both study phases. Conclusion: A university-based research team implementation and dissemination approach seemed to be more effective than a train-the-trainers implementation method in improving dietary intake patterns. This finding suggests that CCCs may need robust educational support beyond their existing internal resources for long-term positive dietary intake pattern changes.